Student Satisfaction Assessment Study of E-Learning Users: User Satisfaction with IT (USIT) - Refki Saputra; M. Amaruna Sahona; Terttiaavin's M.Com (Yayasan Adra Karima Hubbi, 2023)
E-Learning has changed the traditional learning paradigm that is limited to a certain physical space and time. Through eLearning, students can access various educational contents, such as learning modules, learning videos, interactive exercises, and discussion forums, which can be accessed anytime and anywhere by using electronic devices such as computers, laptops, or smartphones.User Satisfaction with IT (USIT) was developed by DeLone and McLean in the context of Information Systems Evaluation in 1992. DeLone and McLean proposed a framework for measuring the success of information systems based on several dimensions including user satisfaction. This USIT framework has undergone development and modification from time to time by researchers and practitioners in the field of Information Systems Evaluation. This study aims to determine the level of satisfaction on the online simulation using the USIT model which is serious in user satisfaction which consists of variables in USIT.This study shows the level of satisfaction of students as e-learning users. It can be concluded that the majority of students are satisfied with their experience using the e-learning platform. This can be seen from the level of positive responses to questions relating to user satisfaction.